Influencing Mechanism of Large-dose of Atorvastatin in Serum Visfatin, MMP-9, and Blood Fat Levels of Patients with Acute Coronary Syndromes: Large-dose of Atorvastatin in Serum Visfatin, MMP-9 and Blood Fat - Ma, Wansheng; Liu, Wenzhao; Mu, Junyu (Cellular and Molecular Biology, 2023)
The research was conducted to analyze the clinical effects and corresponding molecular mechanisms of short-term treatment of acute coronary syndromes (ACS) by different doses of atorvastatin. In the research, a total of 90 ACS patients were included as the samples and divided into an experimental group (conventional treatment+60mg/per time/late atorvastatin), control group 1 (conventional treatment+25mg/per time/late atorvastatin), and control group 2 (25mg/per time/late atorvastatin) according to different doses of atorvastatin. After that, their blood fat and inflammatory factors before and after treatment were analyzed. Total cholesterol (TC) and high-density liptein cholesterol (HDL-C) levels of the experimental group were inferior to those of control groups 1 and 2 in the 5th and 7th days (P<0.05). After treatment, visfatin, matrix metalloproteinase-9 (MMP-9), and brain natriuretic peptide (BNP) of patients in the experimental group and control groups 1 and 2 were notably inferior to those in control groups 1 and 2 (P<0.05). Besides, interleukin-6 (IL-6) and hypersensitive C-reactive protein (hs-CRP) of patients in the experimental group and control groups 1 and 2 were inferior to those in control groups 1 and 2 after treatment (P<0.05). Based on the above results, the short-term treatment by large-dose atorvastatin could reduce blood far and inflammatory factor levels of ACS patients more effectively than by conventional dose, and further inhibit inflammatory reactions and improve patient prognosis with safety and feasibility.